Applicability of Uncertainty analysis to groundwater environmental risks through Fault Tree Analysis and Monte Carlo simulations - Glaude, Robin Francoise (Alma Mater Studiorum - Università di Bologna, 2020)
The Anthropocene epoch initiated by human in uence on its Earth system (biosphere, hydrosphere, .) leads to an irreversible change: Global warming. Climate change alters all existing natural processes, including the ones related to groundwater. The present paper aims to study the occurrence's probability of two particular groundwater risks: the generation of thermokarst lakes in permafrost environment and its subsequent thermal consequences in the surroundings as well as seawater intrusion inducing saltwater contamination in pumping wells. These processes are dependent of physical parameters to which is attached uncertainty. Consequently, two uncertainty analysis methods have been applied to determine the probability of occurence of these undesired events: Fault Tree Analysis and Monte Carlo Simulation. Beside the rough approximation performed to evaluate the probability of thermokarst lake occurence (48%) and of talik development under these latter (73%) by means of fault tree analysis, these high failure probabilities translate the urge to slow down global warming due to the irreversible effect on permafrost environment, meaning its thawing and releasing of trapped methane in the atmosphere. On the other hand, Monte Carlo simulations have been performed to compare dfferent scenarii related to seawater intrusion in Akrotiri aquifer in Cyprus. The results once again translate the disastrous effect of climate change regarding the probability of occurence of these unwanted events. Indeed, a failure probability around 6 times greater (43%) is observed in the climate change scenario with respect to the reference scenario (7%). Uncertainty analysis is good methodology to apply to environmental concerns to quantify the occurence's probability of these undesired events. This would urge public authorities to perform decision making in order to avoid or reduce the failure's probability of these groundwater issues that have irreversible consequences.